2012
DOI: 10.1016/j.tsf.2011.10.174
|View full text |Cite
|
Sign up to set email alerts
|

Resistance switching properties of molybdenum oxide films

Abstract: Resistive random access memory (ReRAM) properties in which the resistance of the insulating material drastically changes by voltage application have recently attracted much attention. In this work, molybdenum oxide prepared by thermal oxidation of Mo films was studied to investigate its potential as a material exhibiting ReRAM switching. The samples oxidized between 400 and 600 o C were composed of MoO 3 and were switchable. Current-to-voltage curves, which were measured in air at room temperature by using a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…15%) may be assigned to the decomposition of the Cp rings of the intercalated metallocene species and condensation of the phosphate groups. The final degradation step takes place in the 700e900 C range (~16%) and the weight loss is consistent with volatilization of MoO 3 formed after 600 C. Volatilization of MoO 3 at those temperatures have been previously observed [27], while Braga et al have reported thermogravimetric analysis data showing that in an inclusion complex of MDC inside b-cyclodextrin all the Mo is volatilized completely well below 1000 C [28].…”
Section: Direct Intercalation and Characterizationsupporting
confidence: 68%
“…15%) may be assigned to the decomposition of the Cp rings of the intercalated metallocene species and condensation of the phosphate groups. The final degradation step takes place in the 700e900 C range (~16%) and the weight loss is consistent with volatilization of MoO 3 formed after 600 C. Volatilization of MoO 3 at those temperatures have been previously observed [27], while Braga et al have reported thermogravimetric analysis data showing that in an inclusion complex of MDC inside b-cyclodextrin all the Mo is volatilized completely well below 1000 C [28].…”
Section: Direct Intercalation and Characterizationsupporting
confidence: 68%
“…The molybdenum oxide (MoO x )-based device with the Cu electrode investigated in this report is a type of CBRAM, 29 while MoO x shows ReRAM switching behaviour even without the Cu electrode. 30 Here, the ReRAM operation of the Cu/MoO x /TiN structure is briefly described based on the assumption of the conventional electrochemical model for the CBRAM, 6,8,12,13 where Cu is the active top electrode (TE) and TiN is the inactive bottom electrode (BE). Application of a positive voltage to the Cu TE induces oxidation of the Cu to produce cations.…”
mentioning
confidence: 99%
“…The current-voltage (I-V) curve exhibits hysteresis that can be exploited in nonvolatile ReRAMs. Since an early report of a Perovskite-type oxide, 7 various materials including binary oxides [8][9][10][11][12][13] and solid electrolytes [14][15][16][17][18][19][20][21][22][23][24] have been reported on this switching operation. The pristine state is typically HRS.…”
mentioning
confidence: 99%